The Acute obstruction of common bile duct - Valls, Alberto; Tchekmedyan, Vartan (Cirugía del Uruguay, 1977)
Among the urgency cases that appear before surgeons, there is the acute obstruction of common bile duct, generally of lithiasic origin. There are two types: 1) With permeable accessory bile duct, which gives rise to acute peritoneal processes, and gallbladder distension due to bile contained -thus differing from obstructive cholecystitis when no bile is contained the rein- which may permeate or flow through a perforation, causing biliary peritonitis; and 2) Non functioning gal! bladder due to obstruction of accessory bile duct; -generally lithiasic- an extremely serious infection with septic shock; general and kidney repercussion and acute renal insufficiency. This results in massive infection of biliary tract ( choliangitis), with angiocholitic abscesses visible by means of cholangiography. This type of picture has been described under the name of acute obstructive supurated cholangitis and very often results in the death of the patient. Knowledge of the exact nature of the obstruction is vital for its urgency treatment, because correct handling of these patients is their sole hope· of survival.